A 12-week Taijiquan practice improves balance control and functional fitness in fall-prone postmenopausal women - Bai, Xiaorong; Xiao, Wensheng; Soh, Kim Geok; Zhang, Yang (Frontiers Media, 2024)
Purpose: Falls are the leading cause of accidental death among older persons, with postmenopausal women facing a greater hazard of falling due to osteoporosis. This study aimed to examine the effects of Taijiquan practice on balance control and functional fitness in at-risk females. Methods: Chinese women who self-reported a tendency to fall and had a baseline one-leg stand test time (4.1 s in the Taijiquan group) below the national average for their age group (60–64 years: 10.9 s, 65–69 years: 9.9 s) were assigned to either a control group (n = 26, mean age = 63.9 years) or a Taijiquan group (n = 24, mean age = 63.9 years). The Taijiquan group participated in a 12-week supervised intervention, while the control group maintained their daily activities. The average duration of each exercise session was 52 min. Static balance and functional fitness were assessed at the beginning and end of the intervention. Results: After 12 weeks, the Taijiquan group significantly outperformed the control group in terms of balance, flexibility, and muscular fitness (all p < 0.05). Participants in the Taijiquan group improved their one-leg stand by 61.0% (+2.5 s, Hedge’s g = 0.85), arm curl by 8.3% (+1.7 repetitions, g = 0.53), handgrip strength by 8.3% (+1.9 kg, g = 0.65), and sit-and-reach by 163.2% (+6.2 cm, g = 1.17). Conclusion: The improvement in balance, coupled with other functional fitness benefits, suggests that Taijiquan could serve as a useful exercise for older women with an elevated risk of falling. Copyright © 2024 Bai, Xiao, Soh and Zhang.